2001
DOI: 10.1677/joe.0.1680079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the presence of OB-Re on leptin radioimmunoassay

Abstract: Leptin, a hormone derived from adipose tissue, regulates energy homeostasis and body weight. In the mouse, serum leptin levels, when measured by radioimmunoassay (RIA), increase by a factor of more than 50 times during pregnancy, compared with those in the non-pregnant state. It is well known that mouse placenta produces the secretory isoform of the leptin receptor, OB-Re. In order to investigate the issue of whether serum leptin levels are actually increased during pregnancy or whether the increased OB-Re con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
3
8
1
Order By: Relevance
“…As expected, ob/ob mice on the KD and the SD had comparable low levels of serum leptin immunoreactivity (Fig. 4D), which probably reflects cross-immunoreactivity with the secretory form of the leptin receptor (21). Likewise, db/db mice on the KD had 430% higher serum ␤HB levels and tended to have higher serum leptin levels than db/db mice on the SD (Fig.…”
Section: Resultssupporting
confidence: 73%
“…As expected, ob/ob mice on the KD and the SD had comparable low levels of serum leptin immunoreactivity (Fig. 4D), which probably reflects cross-immunoreactivity with the secretory form of the leptin receptor (21). Likewise, db/db mice on the KD had 430% higher serum ␤HB levels and tended to have higher serum leptin levels than db/db mice on the SD (Fig.…”
Section: Resultssupporting
confidence: 73%
“…25,31 The latter therefore often displayed artificially increased leptin levels due to the competitive interference of endogenous sOB-R with the binding sites of the antibody.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that secretions of soluble Ob-R, which is a leptin binding protein, into the maternal circulation may lower the rate of leptin clearance and increase plasma leptin concentrations. [6][7][8][9] Thus, we measured maternal parametrial visceral fat leptin mRNA and placental soluble Ob-R mRNA expression. Interestingly, in non-pregnant mice, leptin mRNA expression in visceral fat was not influenced by maternal dietary Zn deficiency and supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that secretions of soluble Ob-R, which is a leptin binding protein, into the maternal circulation may lower the rate of leptin clearance and increase plasma leptin concentrations. [6][7][8][9] …”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation